2001
DOI: 10.1038/nm0901-1057
|View full text |Cite
|
Sign up to set email alerts
|

Activation of natural killer T cells by α-galactosylceramide treatment prevents the onset and recurrence of autoimmune Type 1 diabetes

Abstract: Type 1 diabetes (T1D) in non-obese diabetic (NOD) mice may be favored by immune dysregulation leading to the hyporesponsiveness of regulatory T cells and activation of effector T-helper type 1 (Th1) cells. The immunoregulatory activity of natural killer T (NKT) cells is well documented, and both interleukin (IL)-4 and IL-10 secreted by NKT cells have important roles in mediating this activity. NKT cells are less frequent and display deficient IL-4 responses in both NOD mice and individuals at risk for T1D (ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
520
3
4

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 582 publications
(555 citation statements)
references
References 33 publications
27
520
3
4
Order By: Relevance
“…A similar protection was observed after specific iNKT cell stimulation with exogenous ligands, a-galactosylceramide (a-GalCer) and its analogues [8][9][10][11]. Early reports suggested that iNKT cell protection was associated with the induction of a Th2 response to islet autoantigens [8,[10][11][12]. However, following studies using the transfer of anti-islet T cells showed that iNKT cells inhibit the differentiation of these auto-reactive T cells into effector cells during their priming in pancreatic lymph nodes (PLNs) [13,14].…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…A similar protection was observed after specific iNKT cell stimulation with exogenous ligands, a-galactosylceramide (a-GalCer) and its analogues [8][9][10][11]. Early reports suggested that iNKT cell protection was associated with the induction of a Th2 response to islet autoantigens [8,[10][11][12]. However, following studies using the transfer of anti-islet T cells showed that iNKT cells inhibit the differentiation of these auto-reactive T cells into effector cells during their priming in pancreatic lymph nodes (PLNs) [13,14].…”
Section: Introductionsupporting
confidence: 55%
“…iNKT cells are reduced in number in diabetes-prone NOD mice [4,5], and increasing the number of iNKT cells by adoptive transfer [6,7] or via the introduction of a Va14-Ja18 transgene, reduces significantly the progression of the disease [6]. A similar protection was observed after specific iNKT cell stimulation with exogenous ligands, a-galactosylceramide (a-GalCer) and its analogues [8][9][10][11]. Early reports suggested that iNKT cell protection was associated with the induction of a Th2 response to islet autoantigens [8,[10][11][12].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…iNKT cells are abundant in the liver and rapidly secrete large amounts of immunoregulatory cytokines such as IFN-g and IL-4 after stimulation through their TCR [35][36][37][38][39][40]. Administration of a-GalCer to mice causes rapid release of various cytokines from iNKT cells, which participate in the regulation of various diseases, including tumor rejection and prevention of autoimmune diseases [41][42][43][44][45][46].Although a-GalCer can enhance host resistance against some microbial pathogens [47-55], it remains elusive whether a-GalCer enhances protective immunity against intracellular bacteria.We have recently shown that listeriosis is ameliorated in iNKT-cell-deficient mice [56]. This finding argues against a protective role of iNKT cells in listeriosis.…”
mentioning
confidence: 99%
“…NKT cells are a source of IL-4 and were shown to play a beneficial role in T1D [10][11][12][13]. A deficiency of IL-4 production by NKT cell has been reported in murine models of T1D [14,15] and in human T1D patients [16,17].…”
Section: Introductionmentioning
confidence: 99%